Inspirations from ethnomathematics for the pedagogical practice of teaching geometry - Pissetti , Schayla Letyelle Costa; Soares , Eliana Maria do Sacramento (Seven Editora, 2023)
We bring some ideas that we obtained when developing doctoral research that is in progress, in which we realized that numerous concepts related to geometry were developed, in an empirical and self-taught way, by subjects who work professionally in different places, even if they do not have formal or formal studies. teachers who instruct them in these activities. To analyze and understand this scenario, we took ethnomathematics, understood as an approach that values the mathematical practices and knowledge of cultures and subjects that use it empirically to deal with their daily lives. We illustrate the report with examples that describe how a subject from the wood industry uses his knowledge about geometric concepts in his professional daily life. We conclude by presenting clues so that mathematics teachers can consider the cultural universe of their students, especially when it comes to ideas related to geometry, to think about their teaching performance, highlighting the importance of mathematics teachers to understand that mathematical reasoning is present. In addition to theoretical formalizations, which can often appear in languages other than those used in formal education. DOI:https://doi.org/10.56238/sevened2023.006-038